(untitled) (Hologramática, 2023)
From the first reading of this text, we can find several reasons to consider it a necessary book. Conceived, first of all, to be analyzed at the secondary education level or, in general terms, for readers who love the genre, Mujeres y fantasmas by Dietris Aguilar exhibits attractive features for a young audience: agile reading and short texts. However, the work covers certain topics that make it interesting: death, real places in the suburbs, female monstrosity, among others. The book is subtitled Legends and gender violence, which encourages anchoring in the legendary, but establishes a link with the ESI as a novel proposal. Freud, Saramago, Homer, Graves, Bataille, among other authoritative voices, we try to leave proof that this book is a necessary text.